Expression 5: "y" equals "f" left parenthesis, "x" , "p" , "c" left parenthesis, "g" , right parenthesis , right parenthesis left brace, 0 less than or equal to "x" less than "p" , right bracey=fx,p,cg0≤x<p
5
Expression 6: "y" equals 1 minus "f" left parenthesis, 1 minus "x" , 1 minus "p" , "c" left parenthesis, "g" , right parenthesis , right parenthesis left brace, "p" less than or equal to "x" less than or equal to 1 , right bracey=1−f1−x,1−p,cgp≤x≤1
6
Expression 7: "x" equals "p"x=p
equals=
0.20.2
7
Expression 8: "y" equals "p"y=p
equals=
0.20.2
8
Expression 9: "y" equals left parenthesis, "x" minus "p" , right parenthesis "g" plus "p"y=x−pg+p
9
Expression 10: "y" equals 3 "x" squared minus 2 "x" cubed left brace, 0 less than or equal to "x" less than or equal to 1 , right bracey=3x2−2x30≤x≤1